Racialized Media : The Design, Delivery, and Decoding of Race and Ethnicity - Gonzalez-Lesser, Emma; Hughey, Matthew W. (Matthew Windust) (Book collections on Project MUSE., 2021)
From Black Panther to #OscarsSoWhite, the concept of 'race,' and how it is represented in media, has continued to attract attention in the public eye. In 'Racialized Media', Matthew W. Hughey, Emma Gonzalez-Lesser and the contributors to this important new collection of original essays provide a blueprint to this new, ever-changing media landscape.